Voice quality after thyroplasty type I using a silicone block - Sebova, I.; Ziethe, A.; Döllinger, Michael; Eysholdt, U. (Bratislava Medical Journal, 2019)
AIM: The aim of the work was to evaluate the voice quality of 10 adult patients after thyroplasty type I using a silicone block. Preoperatively patients suffered from unilateral vocal fold paralysis.
CRIS-Team WoS Importer:2019-12-06